HUBUNGAN PENGETAHUAN DENGAN PELAKSANAAN PEMBERIAN ASI EKSKLUSIF PADA IBU YANG MEMILIKI BAYI USIA 0-24 BULAN DI PUSKESMAS BINJAI ESTATE TAHUN 2018 - Irma Handayani (Universitas Prima Indonesia, 2020)
Exclusive breastfeeding is breastfeeding the baby purely, what is meant purely is that the baby is only given breast milk for 6 months without any additional liquid, such as milk, formula, honey, tea, water and without providing additional food, such as bananas, milk porridge , biscuits, porridge or rice team. This study aims to determine the relationship of knowledge with the implementation of exclusive breastfeeding to mothers who have babies aged 0-24 months. This type of research used in this study was analytically with a cross sectional study approach. The number of samples is 30 people. Sampling was done by using Random Sampling Technique with data collection tools using a questionnaire. Data analysis with chi square test. The results showed there was a relationship of knowledge with the implementation of exclusive breastfeeding for mothers with infants aged 0-6 months at the Binjai City Health Center in 2018. For the Binjai City Health Center to actively and routinely conduct counseling about exclusive breastfeeding to the community, especially women of childbearing age and pregnant women, and breastfeeding mothers.